CYTOTOXICITY EFFECTS OF BENALU TEA EXTRACT (SCURRULA OORTINA) ON HELLA CELLS - Hariyadi, Kusumo; Fatmawati, Fatmawati; Subandrate, Subandrate; Aninditia, Fahira; Dzakiyah, Dzakiyah (Biomedical Journal of Indonesia, 2020)
Tea garden waste has been investigated in the form of parasite tea Squrula oortina Species Family: Loranthaceae from the Dempo Pagar Alam tea plantation, Lahat Regency, South Sumatra. Stem and leaf samples are then dried and powdered, then isolated with 70% water-ethanol subfraction. The extract was then dried by vacuum distillation at 70oC until a concentrated extract without ethanol was obtained. The results of the study were tea parasite extract, and the extract was tested for phytochemicals (monounsaturated fatty acids and double, theobromine derivates, quercetin derivates and Epicatekin derivates). Next, it would be taken to the Laboratory of Biological Sciences at Gajah Mada University to be tested for cytotoxic effects on Hella cells, with control positive doxorubicin. The results of the research were tea leaves extract IC50 = 2538 ug/mL and the standard of doxorubicin IC50 = 0.88 ug/mL so that it could be concluded that the parasite of the tea parasite had cytotoxic and proliferative effects.